The influence of product innovation messages on the intention to purchase incumbent products - Kyootai Lee; Eugene Shim; Jiyeon Kim; Hyunjeong Nam (Journal of Innovation & Knowledge (JIK), 2021)
How do product innovation messages delay purchase intentions? Few studies offer answers to this question. Building on the literature of regulatory focus and framing effects, this study aims to identify the mechanism of the relationships among product innovation contents (i.e., performance advancements and price drops), reference time points (i.e., in the past and in the near future), and purchase intentions. Three experiments are conducted in the contexts of electric vehicles (Experiments 1 and 2) and household solar panels (Experiment 3) in South Korea in 2018 and 2019. The results indicate that when prevention-oriented individuals are exposed to prevention-focused messages, as compared to promotion-focused messages, their intentions to purchase incumbent products are weaker. However, promotion-oriented individuals do not exhibit such differences in their purchase intentions. Further, when exposed to promotion-focused messages, promotion-oriented participants have higher purchase intentions when the message is framed as a gain rather than a non-gain. However, when they are exposed to prevention-focused messages, prevention-oriented participants have lower purchase intentions when the message is framed as a loss rather than a non-loss. This study enables the theoretical understanding of how and why consumers respond differently to product innovation messages. It also sheds light on how marketers must strategically manage the messages about innovation outcomes.
Keywords: C90; M31; M37; O33; 650; Regulatory focus; Regulatory fit; Framing effects; Technological advancement; Price drop